RANCANG BANGUN RANGKAIAN PENGONDISI SINYAL SENSOR KAPASITIF PADA SISTEM MONITORING GREENHOUSE DAN FERTIGASI BUAH MELON - Raihan Muhammad Gibran; Eka Maulana; Akhmad Zainuri (Jurnal Mahasiswa TEUB, 2022)
Melon is a widely cultivated fruit because it only takes 60 days until harvest time. One of the biggest threats to melon farmers is crop failure. Melon cultivation in a greenhouse is one solution to overcome this problem. One of the parameters monitored is the water content in the planting media. A non-invasive capacitive sensor is used to read the soil moisture value evenly. This capacitive sensor works like a capacitor, with the planting media as a dielectric material that is placed between the electrode plates. The sensor requires a signal conditioning circuit to convert the capacitance value of the sensor into a DC voltage so that it can be read by the ADC. this circuit has specifications such as: the ability to generate an output in the form of DC voltage, ability to generate different output value for the different condition of planting media, and ability to be read by microcontroller's ADC. The test is carried out on the Signal Conditioning Circuit which consists of: De Sauty bridge circuit, full-wave rectifier circuit, and operational amplifier circuit. The results s